Forceps, Actual Use, and Potential Cesarean Section Prevention: Study in a Selected Mexican Population - Rodrigo Ayala-Yáñez; Paulette Bayona-Soriano; Arturo Hernández-Jimenez; Alejandra Contreras-Rendón; Paulina Chabat-Manzanera; Roberto Nevarez-Bernal (Journal of Pregnancy)
Objective. Assessment of the frequency of complications observed with various forceps and operative vaginal delivery (OVD) techniques performed at the ABC Medical Center (Mexico City) to evaluate their safety, bearing in mind the importance of decreasing our country’s high cesarean section incidence. Methods. We reviewed 5,375 deliveries performed between the years 2007 and 2012, only 146 were delivered by OVD.  Results. Only 1.0% of the cases had a serious, life-threatening situation (uterine rupture). The Simpson forceps was the most favored instrument (46%) due to its simplicity of use, effectiveness, and familiarity. Prophylactic use was the most common indication (30.8%) and significant complications observed were vaginal lacerations (p=0.016), relative risk (RR) of 3.4 (95% confidence interval [CI]: 1.15–10.04), and fourth degree perineal tear (p=0.016), RR of 3.4 (95% CI: 1.15–10.04). Conclusions. Forceps use and other OVD techniques are a safe alternative to be considered, diminishing C-section incidence and its complications.